Structural studies of human GABA-A receptors - Masiulis, S (2017)
Type-A γ-amino-butyric acid receptors (GABAARs) are pentameric ligand-gated ion channels (pLGICs), which mediate the majority of fast inhibitory neurotransmission in the animal central nervous system. Their dysfunction is related to numerous conditions including epilepsy, insomnia, anxiety, panic disorders, depression and schizophrenia. GABAARs are therefore major targets of clinically important drugs, including benzodiazepines and the intravenous general anaesthetics etomidate and propofol, as well as endogenous modulators, for example neurosteroids. Despite recent progress in structural biology of pLGICs, GABAAR structures remain notoriously elusive. Structural information available at the beginning of this project was limited to the benzamidine-bound homopentameric GABAAR-β3, in a desensitised conformation. A large number of fundamental questions, including the molecular architecture of physiological, heteromeric GABAARs, their signalling mechanisms, the binding and action modes of their numerous ligands, remained to be answered. During this DPhil project, I employed structural biology techniques (X-ray crystallography and single particle cryo-electron microscopy) to further the molecular understanding of human GABAARs. I used subunit-specific llama nanobodies to aid crystallization of homomeric GABAA-β3 receptors, which led to a 3.16 Å structure in complex with the general anaesthetic etomidate. This structure elucidates the binding mode of the etomidate, the basis for its subunit selectivity and illustrates conformational changes it triggers. I then used cryo-electron microscopy to determine the first structure of a heteromeric GABAAR, the human α1b3g2, bound to an activating llama nanobody at a medium (5.2 Å) resolution. The numerous other insights obtained range from unambiguously establishing the subunit arrangement and stoichiometry, to proposing a mechanism for receptor assembly and discovering an unexpected role played by N-linked glycans in this process. The work described here opens multiple avenues for future research. Immediate opportunities include high resolution structural characterization of heteromeric GABAARs, via cryo-electron microscopy, further development of nanobodies as novel, high affinity and subunit specific tools to modulate GABA-ergic signalling, and structural characterization of numerous small-molecule modulators, of clinical and physiological relevance, bound to human GABAARs.